Access-based customer journeys - Trujillo-Torres, Lez; Anlamlier, Eda; Mimoun, Laetitia; Chatterjee, Lagnajita; Dion, Delphine (Journal of the Academy of Marketing Science, 2024)
Despite the popularity of access-based platforms, the understanding of customer journeys remains anchored in traditional market contexts that overlook prosumers’ extended value-chain roles, interconnected experiences, and instrumental sociality in access-based consumption. Using a qualitative study on the access-based platform Rent the Runway, the authors discuss the nature of customer journeys in access-based platforms and showcase how customers perform these journeys. The study reveals two key elements: (1) systemic dynamics, which encompass just-in-time circularity and tightly coupled customer interdependencies, and (2) job crafting, which involves customer work practices that allow pain point avoidance, circulation flow adjustments, and journey stickiness increases. Job crafting can create unpredictable disruptions in other customer journeys and affect systemic flows. This investigation expands research on customer experience management and journey design by developing an access-based platform journey model differentiated from ownership- and service-based platform models, showcasing its systemic instability dynamics, and elaborating how to manage these customer journeys.